The Effect of Quality of Work Life and Organizational Justice on Employee Performance at PT Bank Central Asia TBK KCP Teluk Betung - Dunan, Hendri; Felia, Nindy (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to identify, investigate, and assess the impact of quality of work life and organizational justice on employee performance at PT BCA, Tbk Betung Bay Headquarters. The sample for this study consisted of 19 employees from PT BCA, Tbk Betung Bay Headquarters. The justification for using the entire population as the sample is that it represents the full population; if the population is fewer than 100, all individuals are included as study samples. Consequently, the researcher selected all 19 employees as the study sample. This study employed quantitative data analysis, involving the evaluation and interpretation of data through statistical computations to draw conclusions. To facilitate the analysis, the researcher used the SPSS program. The findings of the study indicate that both the quality of work life and organizational justice significantly impact employee performance at PT BCA, Tbk Betung Bay Headquarters.